Controlled low-strength material using industrial hazardous waste incinerator bottom slag and refined kaolin - Naganathan, S.; Razak, H.A.; Hamid, S.N.A. (2008)
The main purpose of this paper is to study the effect of kaolin addition on the performance of Controlled Low-Strength Material (CLSM) made using industrial hazardous waste incinerator bottom slag. Various mix formulatiuons of CLSM were made with the incinerator bottom slag, kaolin, and cement. Amount of cement added varied from 0 to 40 percent of weight of slag. Amount of kaolin added were 25, 50, 75, and 100 percent of weight of cement. Water content was adjusted to get sufficient flowability. The CLSM mixes prepared were tested for setting time, bleeding, and corrosivity in fresh state. Tests like compressive strength, California Bearing Ratio (CBR), Initial Surface Absorption (ISAT), settlement, and water absorption, were conducted on the hardened CLSM. Compressive strength tests were conducted at 7, 14, and 28 days on 70.7 mm cubes. Heavy metals analysis for bleed and leachate water was also conducted on the CLSM mixes. The 28 days compressive strength of CLSM tested ranged from 0.36 to 4.40 MPa. CBR values ranged from 10 to 46, and ISAT values at 1 hour from 0.56 to 4.76 mL/m2/s. None of the twelve heavy metals tested exceeded the threshold limits. It is concluded that the kaolin addition in CLSM using incinerator slag showed reduction in the compressive strength, but improved performance with regard to ISAT, CBR, and water absorption. It is concluded that the incinerator slag can be developed as a new sustainable construction material in CLSM.